2021
DOI: 10.4143/crt.2020.507
|View full text |Cite
|
Sign up to set email alerts
|

Differing Outcomes of Patients with High Hyperdiploidy and ETV6-RUNX1 Rearrangement in Korean Pediatric Precursor B Cell Acute Lymphoblastic Leukemia

Abstract: Recent cooperative trials in pediatric acute lymphoblastic leukemia (ALL) report long-term event-free survival (EFS) of greater than 80%. In this study, we analyzed the outcome and prognostic factors for patients with precursor B cell (Pre-B) ALL (n=405) diagnosed during a ten year period (2005-2015) at our institution. Materials and Methods All patients were treated with a uniform institutional regimen based on four risk groups, except for steroid type; patients diagnosed up till 2008 receiving dexamethasone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The proportion of children with ETV6/RUNX1-positive ALL in this study was 18.2% of ALL in the same period, which is similar to the results in Korea ( 16 ) (23.1%), Greece ( 17 ) (22.7%), Czech Republic ( 18 ) (22%), Turkey ( 19 ) (25.5%), and the United States ( 20 ) (12.8%), but higher than India ( 14 ) (6%), Mexico ( 15 ) (9.6%) and lower than Iran ( 21 ) (34.9) and Europe ( 22 ) (31.5%). The exact reasons for the differences in rates across countries are unclear, and we speculate that they may be due to ethnic differences.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The proportion of children with ETV6/RUNX1-positive ALL in this study was 18.2% of ALL in the same period, which is similar to the results in Korea ( 16 ) (23.1%), Greece ( 17 ) (22.7%), Czech Republic ( 18 ) (22%), Turkey ( 19 ) (25.5%), and the United States ( 20 ) (12.8%), but higher than India ( 14 ) (6%), Mexico ( 15 ) (9.6%) and lower than Iran ( 21 ) (34.9) and Europe ( 22 ) (31.5%). The exact reasons for the differences in rates across countries are unclear, and we speculate that they may be due to ethnic differences.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the multivariate analysis in this study showed that age, WBC, MLL-r gene, and chemotherapy regimen were all independent prognostic factors affecting the prognosis of the B-ALL patients. Age, WBC, and MLL-r gene have been reported to be strongly associated with prognosis in children with B-ALL, all of which can be used as a basis for the risk classification of pediatric ALL ( 16 , 31 33 ). The SCCLG-ALL-2016 protocol currently used by our collaborative group is also considered an independent influence factor on good prognosis, which could be explained by the fact that relative to the GD-ALL-2008 protocol, the SCCLG-ALL-2016 protocol uses monitoring of MRD as a risk adjustment in addition to a comprehensive risk stratification based on clinical and biogenetic characteristics and treatment response to guide treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, prognostic factors of B‐ALL are mainly focused on clinical factors, genetic alterations, and minimal residual disease (MRD) for risk stratification (Inaba & Mullighan, 2020 ). Clinical factors containing age (infant or ≥ 10 years), white blood cell (WBC) count at diagnosis (≥50 × 10 9 /L), central nervous system (CNS) or testicular involvement, race (Hispanic or black), and male sex have been considered adverse prognostic factors (El Ashry et al, 2021 ; Inaba & Mullighan, 2020 ; Lee et al, 2021 ). Genetic alterations such as low hypodiploid, positive E2A‐PBX1 , or KMT2A rearrangement, Philadelphia chromosome‐positive and Ph‐like, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic alterations such as low hypodiploid, positive E2A‐PBX1 , or KMT2A rearrangement, Philadelphia chromosome‐positive and Ph‐like, etc. have been also recognized as worse prognostic factors (Inaba & Mullighan, 2020 ; Lee et al, 2021 ). In addition, positive MRD at end of remission induction was associated with an unfavorable prognosis.…”
Section: Introductionmentioning
confidence: 99%